The Failure of Bartleby Politics in Orwell’s 1984 - Ningtyas, Sulistya (English Department, Faculty of Humanities, Andalas University, 2024)
This study aims to provide a contemporary interpretation of Orwell’s masterpiece, 1984, through the lens of Žižek’s radical violent Act and political withdrawal. Using textual analysis with a psychoanalytic approach, the research examines the failure of Bartleby politics within the protagonist’s journey living in a totalitarian society. Initially, the protagonist commits a radical Act by seeking to rebel against the Party. However, due to the overwhelming power and control exerted by the Party, the protagonist ultimately practices a political withdrawal. Yet, his political withdrawal, commonly referred to as Bartleby politics, is not a mere act of retreat. Rather, it is a strategic decision aimed at preserving his physical existence in the face of imminent destruction. The findings of this study contribute to a deeper understanding of the complexities surrounding political resistance and survival in Orwell’s dystopian world